Analisis Kepuasan Pelanggan Kopi Kapal Api Menggunakan Metode Net Promoter Score - Komharudin, Komharudin; Umami, Nida Auliana; Hidayatulloh, Khairil (JUSTIKA : Jurnal Sistem Informasi Akuntansi, 2025)
This study aims to measure the level of customer satisfaction and customer loyalty of Kapal Api Coffee products launched by Digital Business Students as a Final Exam in the Costumer Behavior course which is a Study Program from Sukabumi Polytechnic which is about understanding how, why, and when consumers make decisions to buy a product or service. This research was conducted on customers of Kapal Api Coffee which aims to calculate the level of satisfaction where the results can be used as a basis for future development. Data collection for this research is through questionnaires distributed to customers. To determine the probability of consumer satisfaction, a customer satisfaction analysis is carried out using the Net Promoter Score (NPS) method.